THE CORRELATION BETWEEN LANGUAGE LEARNING STRATEGIES WITH STUDENTS’ PROFICIENCY - Dwita Laksmita Rachmawati (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2017)
Nowadays, people in Indonesia begin to improve their English ability by learning English both in school and informal institution. Because learning English is different from learning our mother tongue which are completely different in their spelling, pronunciation, and grammar, people have to learn words with strategies to make it easier. Because of that reason, the researcher is interested to investigate the degree of the use of language learning strategies and to find out whether there are any correlation between six categories of language learning strategies used by the students of the first grade at acceleration class of SMA Negeri 5 Malang and their English proficiency. The approach of this study is quantitative related with statistical approach. The population of this research were 60 students on ten grades at acceleration program, senior high school 5, Malang. The data about the strategies that the students used were obtained from Strategy Inventory for Language Learning (SILL) questionnaire completed by the students and their school grade report of the first semester. The result shows that the use of overall language learning strategies falls into medium level. Specifically, the students prefer to use social strategies as the most frequently used, followed by memory, cognitive, affective, metacognitive and compensation strategies. A positive sufficient correlation is found between metacognitive strategies and English proficiency. This sufficient correlation can be examined by looking at the context since English is used as the foreign language in Indonesia. In sum, the students of the first grade at acceleration class are the moderate users of overall language learning strategies. Metacognitive strategies are found as the strategies that correlate with students’ proficiency. Therefore, the teachers of acceleration class should introduce and promote more about the metacognitive strategies to their students in order to increase English proficiency. The researcher also suggest for the readers, especially learners to apply metacognitive strategies because it can improve language skill.